2013
DOI: 10.1155/2013/730734
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Single-Dose and Multidose Administration of the Ethanol Extract of Danshen on CYP3A in Healthy Volunteers

Abstract: The aim of this study was to investigate the effect of single- and multidose administration of the ethanol extract of danshen on in vivo CYP3A activity in healthy volunteers. A sequential, open-label, and three-period pharmacokinetic interaction study design was used based on 12 healthy male individuals. The plasma concentrations of midazolam and its metabolite 1-hydroxymidazolam were measured. Treatment with single dose of the extract caused the mean C max of midazolam to increase by 87% compared with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
(26 reference statements)
0
24
0
Order By: Relevance
“…According to USA Food and Drug Administration's instruction (Food and Drug Administration. 2005), the dose of mg/kg TQPE used in human is approximately mg/day, thus this dose is acceptable for patients compared to other clinical trials used (250-960 mg/day) (Chen et al 2016;Qiu et al 2013;Ried et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…According to USA Food and Drug Administration's instruction (Food and Drug Administration. 2005), the dose of mg/kg TQPE used in human is approximately mg/day, thus this dose is acceptable for patients compared to other clinical trials used (250-960 mg/day) (Chen et al 2016;Qiu et al 2013;Ried et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone I, tanshinone IIA, and cryptotanshinone exihibited weak inhibitory action (IC 50 > 75μM) against CYP2D6 and CYP3A4 (Zhou et al, ). Nevertheless, dihydrotanshinone I is documented to exert a potent inhibitory action towards CYP3A4 with IC 50 value at 1.2–3.2 μM (Qiu et al, ; Wang et al, ). Qiu and co‐workers reported that administration of single dose of the extract (1 g) caused the mean C max of midazolam to increase by 87% compared to that of control.…”
Section: Herbs Administered In Cvd and Their Reported Hdi With Cardiomentioning
confidence: 99%
“…The in vitro study demonstrated that inhibition of CYP3A could be due to dihydrotanshinone I present in the extract, while tanshinone IIA and cryptotanshinone could induce CYP3A. The study indicated that single‐dose administration of danshen extract resulted in inhibition of intestinal CYP3A, but multidose administration can cause induction of intestinal and hepatic CYP3A (Qiu et al, ). A 3‐day treatment of Salvia miltiorrhiza (200 mg/ kg/day) in rats resulted in inhibition of warfarin (2 mg/kg) hydroxylation.…”
Section: Herbs Administered In Cvd and Their Reported Hdi With Cardiomentioning
confidence: 99%
“…The extract from the roots of Salvia miltiorrhiza (danshen) is widely and traditionally used in the treatment of angina pectoris, myocardial infarction, stroke, and cancer in China and other countries [ 2 5 ]. The commercially available preparations from danshen extract are primarily formulated with the ethanol extract, in which the diterpenoid tanshinones accounted for approximately 95% of the total amount with cryptotanshinone, tanshinone IIA, and tanshinone I as the major components [ 6 ]. We found that danshen ethanol extract could induce CYP3A4 in vivo [ 6 ], and the two major components, cryptotanshinone and tanshinone IIA, present in the extract are responsible for CYP3A4 induction via the activation of PXR [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The commercially available preparations from danshen extract are primarily formulated with the ethanol extract, in which the diterpenoid tanshinones accounted for approximately 95% of the total amount with cryptotanshinone, tanshinone IIA, and tanshinone I as the major components [ 6 ]. We found that danshen ethanol extract could induce CYP3A4 in vivo [ 6 ], and the two major components, cryptotanshinone and tanshinone IIA, present in the extract are responsible for CYP3A4 induction via the activation of PXR [ 7 ]. Because CYP3A4 and MDR1 genes have PXR transcriptional binding sites and common molecular mechanism responsible for induction of CYP3A4 and MDR1 by ligand, cryptotanshinone and tanshinone IIA may be assumed to induce MDR1 (also called P-glycoprotein, P-gp) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%